Investigating the efficacy of the application of tension-reducing suture technique in maxillofacial plastic and cosmetic surgery - Du, Yang; Yang, Jiang N.; Liao, Zhi G.; Fu, De Y. (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to explore the application effect of tension-reducing suture technique in maxillofacial plastic surgery.MethodsThe clinical data of 80 patients with maxillofacial trauma who underwent plastic surgery and cosmetic suture in the outpatient operating room of our hospital from March 2022 to March 2024 were retrospectively analyzed. The experimental group used tension-reducing suture technology, while the control group used traditional suture technology. The patients were divided into two groups according to the type of suture, with 40 cases in each group. The two groups were compared in terms of perioperative indicators, complication rate, total satisfaction rate, scar width, and scar quality indicators.ResultsThe perioperative indexes, complication rates, and total satisfaction rate of the experimental group after surgery were significantly different from those of the control group (P < 0.05). The VSS scores of the experimental group were also significantly lower at 1, 3, 6, 12 months after surgery (P < 0.05).ConclusionThe tension-relieving suture technique has significant advantages in maxillofacial plastic surgery. It can effectively reduce surgical complications, reduce scar width, improve patients' scar appearance score, improve the total quality of life score and treatment satisfaction, and is worthy of clinical promotion.